Sources partitioning in the diet of the shipworm Bankia carinata (J.E. Gray, 1827): An experimental study based on stable isotopes. (November 2018) - Charles, François; Sauriau, Pierre-Guy; Aubert, Fabien; Lebreton, Benoît; Lantoine, François; Riera, Pascal
Abstract: Adaptations that allow teredinids to maintain and thrive on wood, a nutritionally unbalanced food, make these marine bivalves remarkable. Capable of filter-feeding, shipworms house endosymbiotic bacteria synthesizing cellulolytic enzymes for digestion of wood carbohydrates and providing nitrogen to their host through nitrogen fixation. To what extent each of these nutrition modes contributes to the shipworm's metabolism remains an open question. In this experimental study, we estimated source partitioning through the determination of δ 13 C and δ 15 N values in original biological samples. For this purpose, pieces of common alder ( Alnus glutinosa ) were immersed at a coastal station of the north-western Mediterranean Sea. The shipworm Bankia carinata infected wood logs and stable isotope mixing models suggested it got most of the carbon and nitrogen it needs from separate sources. From 71 to 77% of the carbon was derived from the digestion of wood carbohydrates, whereas between 42 and 82% of the nitrogen originated from N2 fixation. These first semi-quantitative estimations suggest that the contribution of N2 fixers to nitrogen requirements of this shipworm species is far from incidental. Graphical abstract: Highlights: Nearly all teredinid mollusks are obligate wood eaters. Food sources partitioning in the diet of Bankia carinata was investigated based on stable isotope analysis. The shipworms get the carbon and nitrogen they need from separate sources. δ 13 C values strongly suggest that most carbon is derived from wood. Stable isotope mixing models indicate that N2 fixed by endosymbionts provides at least half of the nitrogen content of the bivalves.